2015
DOI: 10.7567/jjap.54.04dc18
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of electron–electron scattering for hot-carrier degradation

Abstract: Using our physics based model for hot-carrier degradation (HCD) we analyze the importance of the effect of electron–electron scattering (EES) on HCD in transistors with different channel lengths. The model is based on a thorough treatment of carrier transport and is implemented into the deterministic Boltzmann transport equation solver ViennaSHE. Two competing mechanism of Si–H bond-breakage are captured by the model: the one triggered by the multiple vibrational excitation of the bond and another which is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A possible explanation for this change of the temperature behavior (which was suggested to occur at channel lengths less than ∼100 nm) is that in scaled devices carrier-carrier interactions become the dominant scattering mechanism, while other scattering mechanisms are suppressed [14,15]. Carrier-carrier interactions are considered to populate the high energetic tail of the carrier spectrum [14,[16][17][18][19] -i.e., accelerate HCD -and the rate of this process is an increasing function of T . However, recent findings have demonstrated that the temperature dependence of HCD is nonuniversal and is determined by the device geometry and stress conditions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this change of the temperature behavior (which was suggested to occur at channel lengths less than ∼100 nm) is that in scaled devices carrier-carrier interactions become the dominant scattering mechanism, while other scattering mechanisms are suppressed [14,15]. Carrier-carrier interactions are considered to populate the high energetic tail of the carrier spectrum [14,[16][17][18][19] -i.e., accelerate HCD -and the rate of this process is an increasing function of T . However, recent findings have demonstrated that the temperature dependence of HCD is nonuniversal and is determined by the device geometry and stress conditions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…xvii 2-12 A schematic representation of combinations of MVE-and ABmechanisms. It means that the bond can be firstly excited to an intermediate level i by several colder carriers and then dissociated by a solitary high energetical carrier [112].…”
Section: -11mentioning
confidence: 99%
“…This is referred to as the MVE process [105], [110], [111]. With a modification in the model, the real scenario of the Si-H bond breakage comprises a combination of the single-and multiple-carrier processes, as shown in Figure 2-12 [112].…”
Section: Physical Mechanisms For Hcdmentioning
confidence: 99%